(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Travel literature is travel writing of literary value. It is literature written in various languages which faithfully portrays experiences of an author visiting a place for the pleasure of travel. An individual work is sometimes called a travelogue or itinerary. Travel literature may be cross-cultural or transnational in focus, or may involve travel to different regions within the same country. India has been a favourite destination for people all over the world. It has been frequently visited by a lot many writers among whom a few are renowned travel writers of this century. Two among them are William Dalrymple and V.S.Naipaul who have visited India every now and then and have also penned down their reflections in form of travel memoirs that leaves us amazed because of the minute and critical observation of the country.